ApoE knockout rabbits: A novel model for the study of human hyperlipidemia. (February 2016) - Niimi, Manabu; Yang, Dongshan; Kitajima, Shuji; Ning, Bo; Wang, Chuan; Li, Shen; Liu, Enqi; Zhang, Jifeng; Eugene Chen, Y.; Fan, Jianglin
Abstract: Objective: Rabbits are one of the best animal models for the study of hyperlipidemia and atherosclerosis. Although many transgenic rabbits have been created, the development of gene knockout (KO) rabbits has been impossible due to the lack of rabbit embryonic stem cells. We along with others recently generated KO rabbits using genome editing techniques. In the current study, we characterized the lipoprotein profiles of apoE KO rabbits on both chow and cholesterol diets and investigated their susceptibility to a diet-induced atherosclerosis. Approach and results: We analyzed plasma lipids and lipoproteins of apoE KO rabbits and compared them with those of wild-type rabbits. On a chow diet, homozygous (but not heterozygous) apoE KO rabbits showed mild hyperlipidemia and, when challenged with a cholesterol diet, they showed greater susceptibility to diet-induced hyperlipidemia than did the wild-type rabbits and their plasma total cholesterol levels were remarkably increased (1070 ± 61 mg/dL in apoE KO vs. 169 ± 79 mg/dL in the wild type, p< 0.001). Hyperlipidemia in apoE KO rabbits was caused by elevated remnant lipoproteins. Interestingly, increased remnant lipoproteins in apoE KO rabbits were predominated by apoB-48 and rich in both apoA-I and apoA-IV contents. Furthermore, apoE KO rabbits developed greater aortic atherosclerosis than wild-type rabbits when fed with a cholesterol diet for 10 weeks. Conclusions: To our knowledge, this is the first report of generating KO rabbits for the study of lipid and lipoprotein metabolism. ApoE KO rabbits should be a useful model for the study of human hyperlipidemia and atherosclerosis. Highlights: The first KO rabbit model for the study of hyperlipidemia and atherosclerosis. ApoE plays an important role in maintaining cholesterol homeostasis. ApoE KO rabbits will become a new model for the study of human lipoprotein metabolism and atherosclerosis.